Cooperation between hydrogenation and acidic sites in Cu-based catalyst for selective conversion of furfural to γ-valerolactone. (1st June 2021) - Shao, Yuewen; Li, Qingyin; Dong, Xinyi; Wang, Junzhe; Sun, Kai; Zhang, Lijun; Zhang, Shu; Xu, Leilei; Yuan, Xiangzhou; Hu, Xun
Graphical abstract: Selective conversion of furfural into GVL was achieved under the presence of both hydrogenation sites and Brønsted acidic sites. Highlights: Conversion of furfural to γ-valerolactone (GVL) with high yield was achieved. CuAl catalyst catalyzed the hydrogenation of furfural to furfuryl alcohol (FA). Brønsted acidic sites facilitated the alcoholysis of FA to form ethyl levulinate. The co-exist of hydrogenation and acidic sites facilitates the formation of GVL. Abstract: The production of γ-valerolactone (GVL) receives increasing attention due to its extensive applications as a promising fuel and fuel additive. In this study, the direct conversion of biomass-derived furfural to GVL with a unprecedent yield of 90.5% was achieved via consecutive hydrogenation and acid-catalyzed reactions over CuAl for hydrogenation and a co-catalyst (i.e. H-ZSM-5) for acid-catalysis in ethanol. The relative abundance of the hydrogenation sites and acidic sites determines the reaction network and the transfer of the main products from furfuryl alcohol (FA) to ethyl levulinate (EL) or GVL, as the acidic sites, especially the Brønsted acidic sites, not only catalyze the formation of EL from FA, but also affect the hydrogenation activity of CuAl. However, the Lewis acidic sites facilitate the opening ring of FA to 1, 4-pentanediol, preventing the GVL formation. The acid catalyst and hydrogenation catalyst deactivate via varied mechanisms in the conversion of furfural to GVL, which is required to be considered in the further development of the robust catalysts.